1998
DOI: 10.1136/hrt.79.6.619
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac involvement in proximal myotonic myopathy

Abstract: Proximal myotonic myopathy (PROMM) is a recently described autosomal dominantly inherited disorder resulting in proximal muscle weakness, myotonia, and cataracts. A few patients with cardiac involvement (sinus bradycardia, supraventricular bigeminy, conduction abnormalities) have been reported. The cases of three relatives with PROMM (weakness of neck flexors and proximal extremity muscles, calf hypertrophy, myotonia, cataracts) are reported: a 54 year old man, his 73 year old mother, and 66 year old aunt. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 9 publications
1
14
0
1
Order By: Relevance
“…[1][2][3][4][5][6][7][8] However, the affected family members described in this study demonstrated a remarkably benign clinical pattern. They have a structurally normal heart, asymptomatic bradycardia, and excellent exercise tolerance; therefore, no pacemaker implantation was required in this family.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] However, the affected family members described in this study demonstrated a remarkably benign clinical pattern. They have a structurally normal heart, asymptomatic bradycardia, and excellent exercise tolerance; therefore, no pacemaker implantation was required in this family.…”
Section: Discussionmentioning
confidence: 99%
“…Involvement of cardiac conduction may also occur in atypical cases [64] as well atypical cases with PROMM and primary hyperparathyroidism have been reported [50].…”
Section: Progressive Myotonic Myopathies With Multiorgan Dysfunction mentioning
confidence: 97%
“…Reports have also described atypical cases of PROMM in which the DM2 mutation analysis was not performed [4,9,13,44,46,50,52,55,64]. DM2 represents a spectrum of clinical manifestations.…”
mentioning
confidence: 93%
“…In a recent prospective study, 51% of 49 DM1 patients with a prophylactic pacemaker implant developed complete atrioventricular conduction block during a follow‐up of 51 months 20. In DM2/PROMM, involvement of the cardiac conduction system usually seems more benign,23 but severe forms of cardiomyopathy have been reported 38…”
mentioning
confidence: 99%